Implementación de la Iniciativa HEARTS en Argentina: primeros resultados - Rodriguez, Gonzalo (2022)
Cardiovascular diseases are the leading cause of mortality and morbidity in the Region of the Americas, and hypertension is one of the main risk factors. In 2018, Argentina began implementing the HEARTS Initiative in five primary health care centers, through the National Plan for the Prevention and Control of Arterial Hypertension. This study presents the impact its implementation has had on the indicators of effective coverage, treatment, combination therapy, and control. The HEARTS Initiative has multiple components; these include training health teams, reassigning tasks based on the transfer of clinical competencies, providing automatic and clinically validated blood pressure measurement devices, and using a single standardized treatment protocol. A longitudinal data model (generalized estimating equation analysis) was used, and the information from the five health centers was grouped using weighted averages according to the size of the population under coverage. Analysis of the results was stratified into two time periods delimited by the imposition of restrictions due to COVID-19. During the first period of 18 months, significant improvement was observed in treatment (5.9%; p<0.01) and combination therapy (13.4%; p<0.01), with no significant change in coverage (8.4%; p=0.87) and with a paradoxical decrease in control (−3.3%; p=0.02). When the period of restrictions was compared to the previous period, a generalized reduction was observed in all indicators, particularly coverage (−23.6%; p<0.01) and control (−12.5%; p<0.01). However, treatment and combination therapy levels remained above baseline values (1.7%; p<0.01 and 5.4%; p<0.01, respectively).